The effect of SDS micelles on reduction of toluidine blue by ascorbic acid in acid medium - (:unkn) unknown (ELSEVIER, 2006)
The effect of an anionic surfactant, sodium dodecyl sulfate (SDS) from sub-micellar to post-micellar concentrations on the kinetics of reduction reaction of a cationic dye, toluidine blue by ascorbic acid was studied in the absence and presence of 0.1 mol dm(-3) hydrochloric acid (HCl) under pseudo-first order conditions, monitoring the absorbance of toluidine blue at 630 nm. The results were analyzed according to pseudo-phase model of micelles. The reaction was significantly inhibited in the absence of acid, both at very low concentrations and above the critical micelle concentration (CMC) and totally inhibited at the concentration of 2.0 x 10(-2) mol dm(-3) SDS. The pseudo-first order rate constant also decreased with increasing concentration of SDS in the presence of 0.1 mol dm(-3) HCl, but the reaction was not completely inhibited even at the highest concentration. In order to explain the results, the interaction of toluidine blue with SDS was studied separately by means of spectrophotometry as a function of SDS concentration in the absence and presence of 0.1 mol dm(-3) HCl. Spectral data showed that toluidine blue was bound to the micelle in the monomeric form. The binding constants and fraction of micelle-bound toluidine blue to micelles were separately calculated. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: toluidine blue; ascorbic acid; sodium dodecyl sulfate; micellar catalysis; micellar binding constant; AMPHIPHILIC HEMICYANINE DYES; COOMASSIE BRILLIANT BLUE; METHYLENE-BLUE; SPECTROPHOTOMETRIC DETERMINATION; ANIONIC SURFACTANT; HYDROPHOBIC INTERACTION; SULFONEPHTHALEIN DYES; ASSOCIATION; OXIDATION; KINETICS